El principio de la doble conformidad en el sistema penal acusatorio colombiano: análisis desde el paradigma garantista (2021)
This work arises from the criminal dogmatic perspective and from the conception of the guarantism developed by Professor Luigi Ferrajoli, wanting to take as a relevant point the principle of double conformity and its inapplicability in the accusatory criminal system. Thus, a series of moments are denoted: 1. Doctrinally, the subject is not known in depth, since it is relatively new to the application of the Colombian legal system, this does not mean that globally there is a lack or ignorance of this concept, but in Colombia until now the subject is discussed. 2. From the legal perspective, this deficiency is also denoted, since only as of 2014 has the Constitutional Court of the Republic of Colombia pronounced on this phenomenon or legal vacuum. 3. Only until 2018 is a regulation presented that shows the application of the double conformity principle. This text tries to elucidate the context that the principle of double conformity entails, its configuration and its study within the guaranteeist conception as a model of all Social State of Law.